An Community Perspectives in Ethogram for Komodo Dragon (Varanus komodoensis) in the Wild - Fauzia, Alienda M; Kusrini, Mirza Dikari; Mulyani, Yeni Aryati; Sari, Fitri Eka; Nusantara, Muhammad Galih Gurenda; Setiawan, Rezky Agust; Ariefiandy, Achmad (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
The Komodo dragon (Varanus komodoensis) of East Nusa Tenggara, Indonesia, is an endemic species protected by Indonesian law, mostly due to its population size and limited distribution. The natural distribution of the Komodo dragon is limited to Komodo National Park and several areas on the island of Flores and its surroundings. However, increasing population and tourism in its natural habitat might increase the conflict between the Komodo dragon and humans. To study the impact of human activities on the behavior of the Komodo dragon, we constructed an ethogram to catalog the behavioral inventories of the Komodo to enable future quantitative comparison. The Komodo dragon ethogram was obtained from observations in Loh Buaya and Loh Baru Resorts, Rinca Island, Komodo National Park. Observations were made on 10 adult males, 13 adult females, 12 juveniles, and 3 hatchlings Komodo dragons. Data were collected during July-September 2019, February-March 2020, and June-September 2020. Based on observations, observed behavior was grouped into 9 categories based on their function. Among them are sexual behavior, parental behavior, antagonistic behavior, ingestion/egestion, maintenance, movement, resting, and investigative.